Tunisia : Financial System Stability Assessment Update. (IMF Staff Country Reports; Country Report ;, 2006)
From the 2002 Financial Sector Assessment Program (FSAP), a number of structural reforms have been carried out in the financial system. A number of measures have been taken in the regulatory, fiscal, and legal areas to improve credit quality and financial transparency. The stress test confirms the system's vulnerability to a sharp fall in real estate business. The banking sector plays a predominant role in financing the economy. New regulations requiring banks to strengthen credit evaluation and approval procedures are discussed. Measures have been taken to liberalize the capital account.